Reflections and advices on typography - Wilke, Regina Cunha (InfoDesign, 2007)
The book is a concise manual of typography and its applications, a reference to students of design. The publication is divided into three parts: Letter, Text and Grid (translated as diagrama, or diagram, in the Brazilian version). In this sequence, it explores the basic form of letters, the construction of words, the flexible organization of text in rational diagrams and systems. Each essay brings an overview of the historical and technological aspects, and theories, complemented with practical examples of works by recognized graphic designers. The book is complemented by a section with practical advice, including information on the use of dashes, spaces and punctuation, and a short guide to editing and proofreading for designers. In the Brazilian version, this original “Appendix” is entitled “Dicas Úteis” (Useful Tips), and there is a different “Appendix”, with complementary translations, bibliography, index and information about the author.